IDENTIFICATION OF DETECTABLE AREA BY APPLYING INVERSE PROBLEM - Touil Dalal Radia; Lahrech Ahmed Chaouki; Helifa Bachir; Lefkaier Ibn Khaldoun (Journal of Islamic, Social, Economics and Development, 2023)
This work introduces the notion of the GMR sensor's effective area (EA) after being calculated and optimized using the inverse problem (Particle Swarm Optimization method (PSO)).The inverse problem goal function is minimized using (PSO) algorithm to evaluate the detectable area dimensions according to the measurement of the magnetic field strength at the GMR sensor’s location. The operation of the GMR sensor is validated using 3D Finite Element experimental measurements. The prototype of the GMR sensor is developed and tested.